IMPLEMENTATION OF FHIR STANDARD FOR INDONESIAN ELECTRICAL HEALTH RECORD INTEROPERABILITY - Fauziah Hidayat, Inten
The presence of Electrical Health Records (EHR) gives the potential to improve interoperability between health services. Interoperability is the ability of two or more systems to exchange information and to use the information that has been exchanged. The presence of interoperability can provide the information when and where required to meet the patient care needs. However, not all Electronic Health Records have achieved the level of interoperability. Indonesia has also implemented electronic health records developed in Health Information System applications. The development of HIS in Indonesia is still fragmented and built differently among health services. Communication is hard to achieve because the EHR software is built differently among the health service. The interoperability standards have been developed to support interoperability. The use of interoperability standards can act as the middle ground to coordinate between different software systems. Fast Healthcare Interoperability Resource (FHIR) is an interoperability standard developed by HL7 for exchanging healthcare information electronically. FHIR can support syntactic and semantic interoperability upon the concept of Resource and Representational State Transfer Application Programming Interface (REST API). This research aims to implement the FHIR standard on Indonesian Electronic Health Records to achieve interoperability. This study takes the case of a general polyclinic medical record as a research object. We conduct mapping and Gap analysis to see the ability of the FHIR Resource to represent the requirement of medical records in Indonesian general polyclinic. The results of the gap analysis show that the Profile design is needed to provide the specifications for using FHIR Resource following by the requirements of medical records in Indonesian general polyclinic. The next step is designing an interoperable client-server prototype of EHR based on FHIR interoperability that implements the FHIR Resource and REST API to exchange data. Medical record data is exchanged by using FHIR Resource that conforms to Profile specifications. The implementation of the FHIR standard gives the effectiveness and feasibility of Indonesian medical record syntactic interoperability and also supports the use of terminology codes to meet semantic interoperability.